Invisible girl - Hemingway, Mariel (Regan Arts, 2015)
"What is it like to be a teen with depressed addicts for parents, a mentally ill sister, and a grandfather who killed himself? In this moving, compelling diary, Mariel Hemingway writes as her teen self to share her pain, heartache, and coping strategies with young readers."--Provided by publisher.